MERAWAT TULISAN DAN PERLAWANAN PEREMPUAN: TERBITAN BERKALA SEBAGAI RUANG DAN PRAKTIK FEMINIS - Wulandari, Asri Pratiwi; Siscawati, MIa (Paradigma: Jurnal Kajian Budaya, 2025)
Women writers have always contributed to literary development, but their works and thoughts have been structurally forgotten and erased. We conducted this research to unearth women writers' lives, works, and thoughts, which continue to be ignored in literary studies. We use feminist qualitative method and literature review technique to study literary initiatives from women writers in the past such as women-only periodicals. This research uses Virginia Woolf's thoughts as an analytical tool, and our findings show that the women-only space initiative was a response to the mainstream literary ecosystem's lack of support for women writers in various eras and countries. Through feminist initiatives, women writers have responded to the issues of their time and criticized the lack of representation of women and gender lenses in the literary space.